Status of Learning Communication Skills in Undergraduate Medical Education According to Intern's View (Bangladesh Journal of Dental Research & Education, 2013)
This cross sectional descriptive study was done from July 2010-June 2011, in four medical college of Dhaka city. Two government and two private medical colleges were selected according to the convenience of the researcher. One semi structured questionnaire was used to collect the information from the Intern doctors. It contained 26 questions from the variables of communication skills. Researcher himself collected all the data. 218 Intern doctors return the filled up questionnaires on the same day. Allocation of score for response of each item was based on 5 point Likert scale. Study revealed that most of the interns were not taught communication skills in their clinical classes in structured way. But in internship period they felt that those should have taught in structured way. They recommended to teach it as a part of curriculum so every student have equal opportunity to learn these skills.DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16243 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 42-46